Work stress and menstrual patterns among American and Italian nurses - Hatch, M. C.; Figa-Talamanca, I.; Salerno, S. (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'This study assessed whether job stress alters menstrual patterns among nurses working in 2 different settings: a tertiary care hospital in New York (99 nurses) and a university hospital in Rome (25 nurses).' ' METHODS ': 'Data on menstrual patterns were collected by a daily diary in which the nurses recorded their basal body temperature (BBT) and their menstrual bleeding status for a 3-month period. The BBT curves were used to classify cycles as biphasic or monophasic, and as adequate or inadequate with respect to the luteal phase. Job stress was evaluated by both objective (environmental and work characteristics) and subjective (perceived stress) criteria.' ' RESULTS ': 'The American nurses, especially those assigned to high stress units, had an increased risk for long and monophasic cycles [relative risk (RR) 4.3, 95% confidence interval (95% CI) 1.1-16.2 and RR 5.5, 95% CI 1.2-25.5, respectively]. Among those who perceived their stress at work to be high or reported strenuous work activity, the risk for longer cycles was also raised (RR 2.3, 95% CI 0.6-8.0 and RR 1.6, 95% CI 0.7-4.2, respectively). Luteal phase inadequacy followed the same pattern. Similar trends were observed in the Italian data. In addition, the rotating shiftwork pattern prevalent in the Italian group was possibly associated with higher rates of short cycles and inadequate luteal phases when compared with those of nurses working fixed shifts either day or night.' ' CONCLUSION ': 'Menstrual function may be affected by stressful work conditions.
Keywords: menstrual cycle; nurse; reproductive health; stress